Teacher Evaluation and the Professional Development Connection: Perspectives of Special Education Teachers - Kmail, Zaher M.; Brobbey, Gordon (Journal of the American Academy of Special Education Professionals, 2024)
Teacher evaluation has been closely tied to professional development. In special education, professional development experiences are meant to promote special educator learning and implementation of high leverage practices. Yet, the connection between teacher evaluation outcomes and professional development decisions of special educators is largely unexplored. As part of a larger study that examined perceptions regarding the use of existing evaluation systems to assess their practice, this study explored how special educators perceive received feedback and its connection to their professional development needs and choices. The findings reveal a weak correlation between the feedback received in the evaluation process and its influence on professional development decisions and considerations for special educators. They further suggest a lack of encouragement on special educators’ reflective practices or changes made to their teaching. A positive correlation was identified between perceptions about clarity and feedback received, and professional development decisions. Implications for future research are presented.